An Evaluation of the Design Criterion For Sewerage Peak Flow Factor At Segi University Hostel - Ngien, S. K.; Pian, Ng Sook (SEGi, 2013)
Field monitoring of the sewage flows from a sewerage catchment servicing the hostel within SEGi University was performed using an area-velocity flowmeter. The data obtained were processed through the Flowlink software and the results show that the peak flow for the monitored duration occurred at night whereas the daily peak flow occurred on a weekday. The actual per capita flow measured based on the current number of students is 35.6% higher than the design per capita flow stipulated in the Malaysian Standard MS1228:1991. On the other hand, based on the actual per capita flow and actual peak flow from the duration monitored, the actual design criterion obtained is 2.88, lower than the design criterion of 4.7 recommended in MS1228:1991. From the evaluations done, the recommended design criterion for peak flow factor by MS1228:1991 is adequate for a sewerage catchment catering to a population equivalent (PE) similar to this study.